Proses Ekspor PT Bromo Tirta Lestari dengan Komoditi Air Mineral Menggunakan Dry Kontainer pada PT Link Pasipik Indonusa Cabang Surabaya - Wening Nalurita; M Ikhsan Fifadiovan; M. Noor Syamsudin (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to find out in depth the process of exporting mineral water commodities carried out by PT. Bromo Tirta Lestari through the use of dry containers with an FCL (Full Container Load) pattern managed by EMKL services PT. Link Pacific, Indonesia, Surabaya branch. The export process is one of the important aspects in supporting the company's competitiveness in the global market, so it needs to be managed efficiently and in accordance with the provisions of international regulations. In practice, there are several problems that arise. First, the stuffing-by-stuffing process takes a long time due to limited labor and lack of auxiliary tools. Second, delays in the arrival of containers to shippers' warehouses often occur because the location of the depot is far enough so that it hinders smooth operations. Third, the completeness of export documents has proven to be a key factor in the smooth handling of dry containers, because each stage of export requires documents such as Shipping Instruction (SI), Delivery Order (DO), Export Notification of Goods (PEB), Export Service Memorandum (NPE), and Equipment Interchange Receipt (EIR). This study uses a qualitative descriptive method with data collection techniques through observation, interviews, documentation, and literature studies. The results of the study show that increasing the efficiency of stuffing can be done by adding loading and unloading personnel and providing adequate auxiliary equipment. In addition, the timeliness of container arrival can be achieved through better coordination between shippers, EMKL, and trucking parties to make scheduling more precise. The completeness of export documents is also an absolute requirement in ensuring that the entire process runs smoothly without administrative obstacles. Thus, the synergy between shippers, EMKL, and shipping parties greatly determines the success of the mineral water export process.